Adherence to Antihypertensive Medication in Older Adults With Hypertension. Issue 4 (July 2016) - Lo, Suzanne H. S.; Chau, Janita P. C.; Woo, Jean; Thompson, David R.; Choi, Kai Chow
Abstract : Background/Objectives: Effective prevention of cardiovascular events in people with hypertension requires optimal control of blood pressure. Despite advances in management, poor adherence to antihypertensive medications is often reported as the major reason attenuating treatment efficacy. Research has provided limited evidence of associations between illness perceptions, satisfaction with consultations, and medication adherence. The aim of this study is to identify factors significantly associated with medication adherence in a group of Chinese older adults with essential hypertension. Design/Setting/Participants: A cross-sectional correlational study was conducted. Data were collected from 195 older adults (mean [SD] age, 76 [6.6] years) recruited from 12 community centers. Measurements: The Illness Perception Questionnaire–Revised was used to measure illness perceptions, and the Medical Interview Satisfaction Scale was used to measure satisfaction with individual consultations. The Morisky Medication Adherence Scale was used to measure the extent of adherence to antihypertensive medications. Multivariate logistic regression analysis was performed to examine factors, including illness perceptions, consultation satisfaction, and demographic and clinical characteristics, that were significantly associated with medication adherence. Results: More than half of the respondents (55.9%) acknowledged some degree of medication nonadherence. Older age, living alone, and perception related to treatment control were independently associated with increased odds of medication adherence, with odds ratios ranging from 1.14 to 1.92 ( P < .05). Conclusion: The results highlight the importance of cultivating positive beliefs that hypertension is amenable to control by treatment. Furthermore, the adherence behavior of those of younger individuals and living with family should be closely monitored.